Biosorption of Chromium (VI) from Aqueous Solutions by Modified Chitosan Beads - Nguyen , My Linh; Phan , Minh Nhat; Ngo , Hoang Phi Hai (Journal of Technical Education Science, 2016)
The presence of heavy metals pollutants in the industrial effluents has become a serious problem for human beings and the environment. In this work, chitosan beads were crosslinked and modified by Saccharomyces cerevisiae (S. cerevisiae) and histidine to enhance its acid stability and mechanical strength and biosorption capacity. The ability of Chromium (VI) biosorption on chitosan beads modified with Saccharomyces cerevisiae and histidine using glutaraldehyde as a crosslinking agent (SC-HIS-CCB) was studied. Biosorption experiments were performed by varying solution pH (2.0-7.0) and the amount of biosorbent (0.5-5 g L-1). The optimal pH was found to be 4.0. It has been found that the percentage removal efficiency of Cr (VI) increased as the biosorbent dose increased from 10 to 35 mg.g-1.The agigation time is 30 min. The result shows that the modified chitosan beads could be used as an effective biosorbent for the removal of Cr (VI) from wastewater and contaminated water sources.